Internalization of Panca Cinta Values in Curriculum to Foster Character among Islamic Education Program Students, Faculty of Tarbiyah, UIN Ar-Raniry - Lismijar Lismijar; Fakhrul Rijal; Fadhlan Karima (Teunuleh Publisher, 2026)
This study aims to analyze the process and strategies for internalizing the values of Panca Cinta within the curriculum of the Islamic Education Program (PAI), Faculty of Tarbiyah, UIN Ar-Raniry Banda Aceh, in shaping students’ moderate character. This research employs a qualitative approach with a descriptive study design. Data were collected through observation, interviews, and documentation, and then analyzed systematically through data reduction, data display, and conclusion drawing. The findings indicate that the values of Panca Cinta—which include love for Allah and the Prophet, fellow human beings, knowledge, the environment, as well as the nation and homeland have been integrated into the curriculum, both in learning outcomes and across various courses. The process of value internalization occurs through three stages: value transformation, value transaction, and value transinternalization, enabling students not only to understand the values cognitively but also to internalize and practice them in their daily lives. The strategies employed include humanistic learning, lecturers’ role modeling, habituation, reflective dialogue, and reinforcement through co-curricular and extracurricular activities. In addition, the evaluation of value internalization is conducted continuously by emphasizing cognitive, affective, and behavioral aspects. The study also reveals that the implementation of a Panca Cinta-based curriculum has a positive impact on shaping students’ moderate character, as reflected in their tolerance, empathy, responsibility, and ability to live harmoniously in diversity. Thus, the internalization of Panca Cinta values in the PAI curriculum represents an effective approach to developing Islamic education that is humanistic, contextual, and responsive to societal needs.